Pengaruh Budaya Organisasi Terhadap Employee Engagement - Rahayu, Sri; Suhaeni, Tintin (POLITEKNIK NEGERI BANDUNG, 2015)
Engagement at PT Kertas Padalarang (Persero) and the influence of organizational culture on employee engagement. The dimensions of organizational culture are involvement, consistency, adaptability and mission (Denison on Sobirin, 2009: 191). The dimensions of employee engagement are vigor, dedication and absorption (Schaufeli and Bakker, 2003: 5). The sample of this research as much as 151 respondents consists of supervisor, assistant supervisor, main operator, operator, and others (honorary and contract employees) which spreads in accounting, finance, R & D, logistic, marketing, human resources, internal control unit, engineering and production department. The method which used in this research is quantitative research methods. Data analysis method which used are descriptive analysis, classic assumption test, regression analysis, correlation analysis and hypothesis testing. Based on the results, organizational culture is currently in the good category, compare to employee engagement that is still in the moderate category. The relation of organizational culture and employee engagement currently are on strong category. The Regression equation in this research is Y=8,655+0,651X. Therefore, the influence of organizational culture on employee engagement amounted to 45,4%.